2006
DOI: 10.1021/jp0644816
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism and Origin of Exciton Spin Relaxation in CdSe Nanorods

Abstract: The dynamics of exciton spin relaxation in CdSe nanorods of various sizes and shapes are measured by an ultrafast transient polarization grating technique. The measurement of the third-order transient grating (3-TG) signal utilizing linear cross-polarized pump pulses enables us to monitor the history of spin relaxation among the bright exciton states with a total angular momentum of F = +/-1. From the measured exciton spin relaxation dynamics, it is found that the effective mechanism of exciton spin relaxation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
73
2

Year Published

2008
2008
2023
2023

Publication Types

Select...
3
3

Relationship

2
4

Authors

Journals

citations
Cited by 34 publications
(80 citation statements)
references
References 77 publications
5
73
2
Order By: Relevance
“…One exponential, associated with exciton recombination had a long nanosecond timescale that could not be fully resolved in our experiments, which had a maximum pump-probe time delay, t p , of 850 ps. The other two exponentials likely correspond to surface trapping dynamics and were on the order of picoseconds to tens of picoseconds, consistent with previous results [10,31,32,11,12]. The timescales and relative amplitudes obtained from the VVVV data were then used to analyze the VHVH and VHHV traces, allowing us to account for the exciton population relaxation dynamics in the CPH-3TG signals and to obtain the exciton spin flip rate.…”
Section: Resultssupporting
confidence: 79%
See 2 more Smart Citations
“…One exponential, associated with exciton recombination had a long nanosecond timescale that could not be fully resolved in our experiments, which had a maximum pump-probe time delay, t p , of 850 ps. The other two exponentials likely correspond to surface trapping dynamics and were on the order of picoseconds to tens of picoseconds, consistent with previous results [10,31,32,11,12]. The timescales and relative amplitudes obtained from the VVVV data were then used to analyze the VHVH and VHHV traces, allowing us to account for the exciton population relaxation dynamics in the CPH-3TG signals and to obtain the exciton spin flip rate.…”
Section: Resultssupporting
confidence: 79%
“…However, population in the F ¼ 0 state does not directly contribute to the exciton spin flip rate. Instead, it contributes to the overall positive long delay time offset of the CPH-3TG signals [12].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Figure 6b shows a plot of another distinct kind of radiationless relaxation rate in NCs that has been largely overlooked until recently. [111,112] These are the various relaxation pathways within the fine structure states of the lowest exciton. For example, such relaxation processes decide the pathways taken from optical excitation to photoluminescence: say, F ¼ þ1 !…”
Section: Radiationless Relaxation Dynamicsmentioning
confidence: 99%
“…We have found that the time scales for such relaxation processes are strongly pathway dependent and time constants range from 100 s of femtoseconds to 10 s of picoseconds. [112] The specific rate constant plotted in Figure 6b turns out to be strongly dependent only on the diameter of nanocrystals (and not on length at all), [93] which has enabled us to employ this trend as a 'calibration curve' to estimate how exciton size depends on shape in systems like those NCs shown in Figure 1c. [38] Note that the sign of the total angular momentum flips, and it is this phenomenon that enables us to record these dynamics, even though the states involved are completely obscured by inhomogeneous line broadening.…”
Section: Radiationless Relaxation Dynamicsmentioning
confidence: 99%